Interfacial and Foaming Characteristics of Milk Whey Protein and Polysaccharide Mixed Systems - Perez, Adrián Alejandro (2010)
Protein-polysaccharide (PS) interactions find many applications in food engineering and new foam formulations. In this article, we have studied the effect of anionic nonsur-face active PSs [sodium alginate (SA) and lambda-carrageenan (k-C)] in aqueous solution on interfacial and foaming characteristics of milk whey proteins [whey protein concentrate (WPC) and whey protein isolate (WPI)]. Whey protein concentration (1.0% wt), temperature (20 C), pH (7), and ionic strength (0.05 M) of the aqueous media were kept constant, while PS influence was evaluated within a 0.0-1.0% wt concentration range. The dynamic properties (dynamics of adsorption and surface dilatational properties) of WPC/PS and WPI/PS adsorbed films were considered in order to correlate the foaming characteristics of the biopolymer mixed systems. Foaming characteristics of the biopolymer mixed systems depended on the PS relative concentration in the aqueous phase and on the whey protein-PS interactions in solution and at the air-water interface. Dynamic surface properties of the adsorbed films at short adsorption time had a significant effect on foaming capacity. For a particular system, the overall foam destabilization (foam half-life time) and the individual destabilization processes (drainage, disproportionation, and bubble coalescence) depend on the nature of the PS, its relative bulk concentration, and whey protein-PS interactions in the vicinity of the air-water interface. The viscosity of the aqueous phase has an effect on the rate of drainage while the rate of disproportionation/collapse is more dependent on the interfacial characteristics of the adsorbed film.